HYDROGEN DEFECTS ON THE SURFACE OF LEAD-FREE FERROELECTRIC Na\(_{0.5}\)Bi\(_{0.5}\)TiO\(_3\) MATERIALS - Tien Lam Vu; Hoang Thoan Nguyen; Huu Lam Nguyen; Ngoc Trung Nguyen; Quoc Van Duong; Duc Dung Dang (Tạp chí Khoa học Đại học Đà Lạt)
Hydrogen atomic chemisorption and adsorption at all possible vacancy sites on the surface of perovskite Na0.5Bi0.5TiO3 (110) were explored using calculations from density functional theory. Our calculations reveal that a pristine Na0.5Bi0.5TiO3 (110) surface can exhibit direct and indirect transitions characterized by optical bandgaps of 2.68 eV and 2.75 eV, respectively. The density of states of the Na0.5Bi0.5TiO3 (110) surface indicates predominant electron transitions from O-2p valence bands to Ti-3d and Bi-6p conduction bands in the low-energy range. Hydrogen substitution at vacancies can induce magnetism, whereas hydrogen adsorption enhances both the magnetism and conductivity of the surface system. In particular, the charge density reveals electron transfer between cations and hydrogen atoms, providing insight into the variations in hydrogen bonding properties in these surface systems. These observations expand our understanding of hydrogen chemisorption and adsorption on defect sites, providing a novel avenue for investigating and potentially developing environmentally friendly multiferroic materials for advanced electronic devices.